2017
DOI: 10.1016/j.clnu.2016.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Mediterranean diet is associated with lower prevalence of osteoarthritis: Data from the osteoarthritis initiative

Abstract: Summary Background & aims The Mediterranean diet appears to be beneficial for several medical conditions, but data regarding osteoarthritis (OA) are not available. The aim of this study was to investigate if adherence to the Mediterranean diet is associated with a lower prevalence of OA of the knee in a large cohort from North America. Methods 4358 community-dwelling participants (2527 females; mean age: 61.2 years) from the Osteoarthritis Initiative were included. Adherence to the Mediterranean diet was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 36 publications
(39 reference statements)
1
56
0
1
Order By: Relevance
“…Specifically, the daily intake of 25 g dietary total fiber is related to low risk of moderate and severe pain, in eight years follow up 33 . Other results presented fruits, vegetables consumption is associated with healthier lifestyle 19,33 .…”
Section: Fruits Vegetables Cerealsmentioning
confidence: 86%
See 3 more Smart Citations
“…Specifically, the daily intake of 25 g dietary total fiber is related to low risk of moderate and severe pain, in eight years follow up 33 . Other results presented fruits, vegetables consumption is associated with healthier lifestyle 19,33 .…”
Section: Fruits Vegetables Cerealsmentioning
confidence: 86%
“…These factors seem to impact the prevalence of knee OA in people with the highest adherence of MD. It was also observed that evaluating the individual elements of Mediterranean diet only the higher cereal consumption was associated with reduced incidence of knee OA, probably through anti-inflammatory and anti-oxidant properties, due to high content of vitamins and minerals 19 . Veronese and his colleagues, this time, revealed that participants with OA and greater adherence to MD had better status of health and quality of life.…”
Section: The Role Of Mediterranean Diet Against Osteoarthritismentioning
confidence: 91%
See 2 more Smart Citations
“…In a very interesting study by Musumeci et al, for example, it is reported that the consumption of Sicilian extra virgin olive oil, an essential component of MD, in conjugation with regular physical activity, are associated with the reduction of the pro-inflammatory cytokines expression (in particular interleukin-1), and the increased expression of lubricin, a chondroprotective glycoprotein with lubricating properties [7]. Moreover, recently, it has been shown that the adherence to a MD is associated with a lower prevalence of knee OA in a large cohort from North America [8]. In this remarkable and large cross-sectional study by Veronese et al, including 4358 participants with a mean age of 61 years, almost 30% of the cohort presented knee OA, diagnosed both clinically and radiologically.…”
Section: Effects Of Mediterranean Diet On Osteoarthritis Onsetmentioning
confidence: 99%